2000
DOI: 10.1034/j.1600-0536.2000.043003129.x
|View full text |Cite
|
Sign up to set email alerts
|

Pine processionary caterpillar as a new cause of immunologic contact urticaria

Abstract: Nowadays, caterpillars are included among the agents that elicit contact urticaria by a non-immunologic mechanism. Our objective was to find the rôle that an IgE-mediated mechanism could have among patients with suspected contact urticaria from pine processionary caterpillars. 16 patients with suspected contact urticaria from this caterpillar were studied by prick testing and specific IgE detection by immunoblotting. 87% of the patients had a positive prick test and immunoblotting for caterpillar extract. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 10 publications
1
63
0
2
Order By: Relevance
“…It was shown that this protein activates mast cells via a direct non-immunological effect (non-IgE-mediated mediator release) and a type I allergic hypersensitivity reaction (IgE-mediated mediator release) [12]. The existence of a (true) type I allergic hypersensitivity reaction to the larval extracts of the pine processionary caterpillar [12, 13, 14]and the oak processionary caterpillar [12]was confirmed by positive skin prick tests and the determination of specific IgE antibodies. Mechanical irritation from penetration of the setae (foreign body reaction) appears to be a third mechanism which is responsible for the reactions in skin and mucous membranes [10, 11, 12, 13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that this protein activates mast cells via a direct non-immunological effect (non-IgE-mediated mediator release) and a type I allergic hypersensitivity reaction (IgE-mediated mediator release) [12]. The existence of a (true) type I allergic hypersensitivity reaction to the larval extracts of the pine processionary caterpillar [12, 13, 14]and the oak processionary caterpillar [12]was confirmed by positive skin prick tests and the determination of specific IgE antibodies. Mechanical irritation from penetration of the setae (foreign body reaction) appears to be a third mechanism which is responsible for the reactions in skin and mucous membranes [10, 11, 12, 13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…12,14,15 7. CONCLUSIONS Pine processionary cutaneous reactions are common in the human population of South Europe where pine processionary moth is endemic.…”
Section: Treatmentmentioning
confidence: 99%
“…The lesions appear within hours and they can persist for several days. In contact urticaria, there are evanescent itchy papules, often in association with angioedema, particularly on the eyelids 14 and mucosae. 18 Linear and figurated papulo-urticarial lesions are seen in children who let caterpillar stroll on their skin.…”
Section: Cutaneous Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Other signs are conjunctivitis, pharyngitis, malaise and upper respiratory tract symptoms including respiratory distress [1,2,3,8,9,10,11,12,13,14,15]. Few cases of life-threatening anaphylactic reactions have been reported [4, 5].…”
Section: Introductionmentioning
confidence: 99%